Southern Annular Mode drives multicentury wildfire activity in southern South America - Holz, Andrés (2017)
The Southern Annular Mode (SAM) is the main driver of climatevariability at mid to high latitudes in the Southern Hemisphere,affecting wildfire activity, which in turn pollutes the air and contributesto human health problems and mortality, and potentiallyprovides strong feedback to the climate system through emissionsand land cover changes. Here we report the largest Southern Hemispherenetwork of annually resolved tree ring fire histories, consistingof 1,767 fire-scarred trees from 97 sites (from 22 °S to 54 °S) in southernSouth America (SAS), to quantify the coupling of SAM and regionalwildfire variability using recently created multicentury proxyindices of SAM for the years 1531?2010 AD. We show that at interannualtime scales, as well as at multidecadal time scales across 37?54 °S,latitudinal gradient elevated wildfire activity is synchronous with positivephases of the SAM over the years 1665?1995. Positive phases ofthe SAM are associated primarily with warm conditions in thesebiomass-rich forests, in which widespread fire activity depends on fueldesiccation. Climate modeling studies indicate that greenhouse gaseswill force SAM into its positive phase even if stratospheric ozonereturns to normal levels, so that climate conditions conducive to widespreadfire activity in SAS will continue throughout the 21st century.